Democratization and real exchange rates - Benjamin Furlan; Martin Gächter; Bob Krebs; Harald Oberhofer (University of Salzburg, Department of Social Sciences and Economics, 2012)
This paper empirically assesses how democratization affects real exchange rates. Specifically, in line with the democratic peace theory we argue that democratization reduces currency undervaluation, and thus, might bring misalignments in foreign exchange markets to an end. We test this hypothesis for a sample of countries observed from 1980 to 2007. Econometrically, we combine a difference-in-difference (DID) approach with propensity score matching estimators. Our estimation results reveal that democratization causes real exchange rates to appreciate, lending empirical support to the democratic peace theory in this specific economic context.
Keywords: C21; C23; F02; F31; F59; N20; 330; Real exchange rates; democratization; democratic peace theory; difference-in-differences-estimator; matching estimators